2014
DOI: 10.1007/s00204-014-1278-7
|View full text |Cite
|
Sign up to set email alerts
|

Raising awareness of new psychoactive substances: chemical analysis and in vitro toxicity screening of ‘legal high’ packages containing synthetic cathinones

Abstract: The world's status quo on recreational drugs has dramatically changed in recent years due to the rapid emergence of new psychoactive substances (NPS), represented by new narcotic or psychotropic drugs, in pure form or in preparation, which are not controlled by international conventions, but that may pose a public health threat comparable with that posed by substances listed in these conventions. These NPS, also known as 'legal highs' or 'smart drugs', are typically sold via Internet or 'smartshops' as legal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 63 publications
1
63
0
1
Order By: Relevance
“…Benzocaine was also reported as a cutting agent for the synthetic cathinone flephedrone [22]. Studies on the composition of legal highs' marketed in Portugal, prior to being illegal, reported that products were usually mixtures of synthetic cathinones and several other ingredients such as glucose, lactose and caffeine [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Benzocaine was also reported as a cutting agent for the synthetic cathinone flephedrone [22]. Studies on the composition of legal highs' marketed in Portugal, prior to being illegal, reported that products were usually mixtures of synthetic cathinones and several other ingredients such as glucose, lactose and caffeine [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous cases of delirium have been described, with hallucinations, agitation and aggressiveness associated with adrenergic symptomatology such as tachycardia, hypertension, restlessness, sweating and pupil dilatation, among others. It has recently been demonstrated that second generation SCAs have a high hepatotoxic potential (Araújo, Valente et al, 2015). Likewise, severe psychopathology has been associated with these substances, including mood swings and suicidal behavior, anxiety, hallucinations and paranoid ideation.…”
Section: Synthetic Cathinonesmentioning
confidence: 99%
“…All synthetic cathinones are chiral and can exist in two stereoisomer forms. In Europe and the USA, the most commonly used cathinones were: 4-methylmethcathinone (mephedrone; "Meow/Miaow Miaow," "4-MMC," "MMCat," "Meph," "Rush," "Crab"), methylone, 4-methylethcathinone (4-MEC), 3,4-methylenedioxypyrovalerone (MDPV; "Cherry Coke," "Doves Red," "Hurricane Charlie," "Sextasy," "Stardust," "Xtacy"), pentedrone, α-pyrovalerone (Araújo et al, 2014;EMCDDA, 2014b, Helander et al, 2014Maxwell, 2014;Zawilska & Wojcieszak, 2013;Zuba & Byrska, 2013). Detailed information on chemical structures and the analytical methods for cathinones detection is provided by Paillet-Loilier, Cesbon, Le Boisselier, Jourgine, and Debruyene (2014).…”
Section: Psychostimulantsmentioning
confidence: 99%
“…Although the prevalence and pattern of NPS use differ between various countries, the most popular groups are SCs and psychostimulants (Araújo et al, 2014;Deluca et al, 2012;EMCDDA, 2013EMCDDA, , 2014aHelander, Bäckberg, Hultén, Al-Saffar, & Beck, 2014;Maxwell, 2014;UNODC, 2013). Both groups are described in this chapter.…”
Section: Introductionmentioning
confidence: 99%